Analyzing the impact of corruption on economic growth according to the difference in exports’ structure - Lazhar, Labed; Mohamed Ridha, Boucenna; Imen, Kemmouche (Dirassat Journal Economic Issue, 2021)
This study aims to analyze the impact of corruption on economic growth and the form of that effect according to the difference in the export structure of 79 countries, during the period 2012/2018, which were divided into four groups, according to the UNCTAD classification. The analysis is based on the panel data model. Which was estimated using the STATA 16 software. The study found a variety of effects due to export structure differences. It was found that corruption has a significant negative impact on oil and minerals exporters’ countries, while it had no significant effect on industrial and agricultural products exporters’ countries. Therefore, the most important recommendation that can be made here is that there is no unified anti-corruption policy among countries to follow. Rather, the country’s export structure is of major importance in generating solution components of that anti-corruption policy.